Proposition of Potential GSK-3β Inhibitors for the Treatment of Alzheimer’s Disease: A Molecular Modeling Study - Castro, Leandro L.; Picanço, Leide C. S.; Silva, Jaderson V.; Souza, Lucilene R.; Sousa, Kessia P. A.; Pinheiro, Abraão A.; Chaves, Gisele A.; Teixeira, Hueldem R. C.; Silva, Guilherme M.; Taft, Carlton A.; de P. da Silva, Carlos H.T.; da S. Hage-Melim, Lorane I. (Current Computer - Aided Drug Design, 2020)
Introduction: The enzyme Glycogen Synthase Kinase 3-β (GSK-3β) is related to neuronal cell degeneration, representing a promising target to treat Alzheimer’s Disease (AD). Methods: In this work, we performed a molecular modeling study of existing GSK-3β inhibitors by means of evaluation of their IC50 values, derivation of a pharmacophore model, molecular docking simulations, ADME/Tox properties predictions, molecular modifications and prediction of synthetic viability. Results: In this manner, inhibitor 15 (CID 57399952) was elected a template molecule, since it demonstrated to bear relevant structural groups able to interact with GSK-3β, and also presented favorable ADME/Tox predicted properties, except for mutagenicity. Based on this inhibitor chemical structure we proposed six analogues that presented the absence of alerts for mutagenic and carcinogenic activity, both for rats and mouse; likewise they all presented low risk alerts for inhibition of hERG and medium prediction of synthetic viability. Conclusion: It is concluded that the analogues of GSK-3β inhibitors were optimized in relation to the toxicity endpoint of the template molecule, being, therefore, presented as novel and promising drug candidates for AD treatment.
Keywords: GSK-3β